Insulin-resistance HCV infection-related affects vascular stiffness in normotensives. Issue 1 (January 2015) - Perticone, Maria; Maio, Raffaele; Tassone, Eliezer Joseph; Tripepi, Giovanni; Di Cello, Serena; Miceli, Sofia; Caroleo, Benedetto; Sciacqua, Angela; Licata, Anna; Sesti, Giorgio; Perticone, Francesco
Abstract Background and Aims. Arterial stiffness evaluated as pulse wave velocity, is an early marker of vascular damage and an independent predictor for cardiovascular events. We investigated if the insulin resistance/hyperinsulinemia chronic hepatitis C virus infection-related could influence arterial stiffness. Methods. We enrolled 260 outpatients matched for age, body mass index, gender, ethnicity: 52 with never-treated uncomplicated chronic hepatitis C virus infection (HCV+), 104 never-treated hypertensives (HT) and 104 healthy subjects (NT). Pulse wave velocity was evaluated by a validated system employing high-fidelity applanation tonometry. We also measured: fasting plasma glucose and insulin, total, LDL- and HDL-cholesterol, triglyceride, creatinine, e-GFR-EPI, HOMA, quantitative HCV-RNA. Results. HCV+ patients with respect to NT had an increased pulse wave velocity (7.9 ± 2.1 vs 6.4 ± 2.1 m/s; P < 0.0001), similar to that observed in HT group (8.8 ± 3.2 m/s). HCV+ patients, in comparison with NT, had higher triglyceride, creatinine, fasting insulin and HOMA (3.2 ± 1.3 vs 2.5 ± 1.0; P < 0.0001). At linear regression analysis, the correlation between pulse wave velocity and HOMA was similar in HT (r = 0.380, P < 0.0001) and HCV+ (r = 0.369, P = 0.004) groups. At multiple regression analysis, HOMA resulted the major determinant of pulse wave velocity in all groups, explaining respectively 11.8%, 14.4% and 13.6% of its variation in NT, HT and HCV+. At correlational analysis hepatitis C virus-RNA and HOMA demonstrated a strong and linear relationship between them, explaining the 72.4% of their variation (P = 0.022). Conclusions. We demonstrated a significant and direct correlation between HOMA and pulse wave velocity in HCV+ patients, similar to that observed in hypertensives.